Quantification of training load in Canadian football: Application of session-RPE in collision-based team sports - Clarke, N.; Farthing, J. P.; Norris, S. R.; Arnold, B. E.; Lanovaz, J. L. (The Journal of Strength and Conditioning Research, 2013)
The session-rating of perceived exertion (Session-RPE) method for quantifying internal training load (TL) has proven to be a highly valuable and accurate monitoring tool in numerous team sports. However, the influence of frequent impact during Canadian football on the validity of this subjective rating tool remains unclear. The aim of this study was to validate Session-RPE application to a prolonged, intermittent, high-intensity collision-based team sport through correlation of internal TL data collected using 2 criterion heart rate-based measures known as Polar Training-Impulse (TRIMP) and Edwards' TL. Twenty male participants (age = 22.0 ± 1.4 years) from the competitive roster of the University of Saskatchewan Canadian football team were recruited. Session-RPE, Polar TRIMP, and Edwards' TL data were collected daily over the 2011 Canadian Interuniversity Sport pre-competitive and competitive season (11 weeks; 713 total practice sessions). On average, each player contributed 36 sessions of data to the analysis. Statistically significant correlations (p < 0.01) between Session-RPE with Polar TRIMP (r = 0.65-0.91) and with Edwards' TL (r = 0.69-0.91) were found for all individual players. This study provides confirmation that Session-RPE is an inexpensive and simple tool, which is highly practical and accurately measures an individual's response (internal TL) to the Canadian football practice. Furthermore, when considering the number of individuals involved worldwide in collision-based team sports, this tool has the potential to impact a large proportion of the global sporting community.